KOORDINASI CAMAT DALAM PROSES PEMBANGUNAN DI KECAMATAN BUNGKU TENGAH KABUPATEN MOROWALI - Fatmawati Fatmawati (Katalogis, 2018)
This study aims to identify and explain the coordination of subdistrict heads in the development process in the district of Central Bungku district of Morowali. The location of the research was conducted at the Bungku Tengah District Office of Morowali District. The theory used is coordination according to Hasibuan (2006: 86-87), coordination is divided into two major parts of vertical coordination and horizontal coordination ". This research is descriptive research using qualitative approach. The research informant was determined using purposive technique. The research informants determined by the researcher amounted to 7. The type of data used consisted of primary data and secondary data. Data collection is done by Observation, Interview, and Documentation. Data analysis is done by Data Reduction, Data Presentation, and Drawing Conclusion. The results of Coordination of Camat In Development Process In Sub-district of Bungku Tengah Morowali District has not been done well overall, because of 2 (two) types of coordination according to Hasibuan which used as benchmark, there is still one coordination that has not been done well that is Horizontal coordination. While the coordination that has been done well is Vertical Coordination.